Accelerating of the electrons of electron bunches in a waveguide loaded dielectric structure - Linnik, A.F.; Onishchenko, I.N.; Omelayenko, O.L.; Pristupa, V.I.; Sotnikov, G.V.; Us, V.S. (Вопросы атомной науки и техники, 2021)
The paper presents some results of experimental studies of the excitation of wake fields and the acceleration of electrons in waveguide-dielectric structures (DS) upon injection of a sequence of electron bunches into them. Experiments have shown an increase in the amplitude of the wake wave and the acceleration of a small fraction of electrons when the wavelength of the excited field is equal to the doubled bunch length. A simple physical model of the observed phenomenon is given. Also, the paper proposes a method for accelerating a part of each electron bunch in the steady-state mode of the resonator dielectric structure. Some of the electrons are “cut out” by the collimator and enter the accelerating phase of the previously excited wake wave. The wave is displaced due to the difference in the distances traveled by the wave and the accelerated part of the electrons.